Homeostatic model of human thermoregulation with bi-stability - Hajnová, Veronika; Zlámal, Filip; Lenárt, Peter; Bienertova-Vasku, Julie (Scientific reports, 2021)
All homoiothermic organisms are capable of maintaining a stable body temperature using various negative feedback mechanisms. However, current models cannot satisfactorily describe the thermal adaptation of homoiothermic living systems in a physiologically meaningful way. Previously, we introduced stress entropic load, a novel variable designed to quantify adaptation costs, i.e. the stress of the organism, using a thermodynamic approach. In this study, we use stress entropic load as a starting point for the construction of a novel dynamical model of human thermoregulation. This model exhibits bi-stable mechanisms, a physiologically plausible features which has thus far not been demonstrated using a mathematical model. This finding allows us to predict critical points at which a living system, in this case a human body, may proceed towards two stabilities, only one of which is compatible with being alive. In the future, this may allow us to quantify not only the direction but rather the extent of therapeutic intervention in critical care patients.
Keywords: Animals; homeostáza; biologické modely; Acclimatization; teoretické modely; tělesná teplota; lidé; Models, Biological; Homeostasis; fyziologická adaptace; aklimatizace; Body Temperature Regulation; Male; Body Temperature; Adaptation, Physiological; Thermodynamics; termoregulace; zvířata; mužské pohlaví; termodynamika; Models, Theoretical; Humans